Biofunctionalization of metallic implants by calcium phosphate coatings - Yingchao Su; Irsalan Cockerill; Yufeng Zheng; Liping Tang; Yi-Xian Qin; Donghui Zhu (Bioactive Materials, 2019)
Metallic materials have been extensively applied in clinical practice due to their unique mechanical properties and durability. Recent years have witnessed broad interests and advances on surface functionalization of metallic implants for high-performance biofunctions. Calcium phosphates (CaPs) are the major inorganic component of bone tissues, and thus owning inherent biocompatibility and osseointegration properties. As such, they have been widely used in clinical orthopedics and dentistry. The new emergence of surface functionalization on metallic implants with CaP coatings shows promise for a combination of mechanical properties from metals and various biofunctions from CaPs. This review provides a brief summary of state-of-art of surface biofunctionalization on implantable metals by CaP coatings. We first glance over different types of CaPs with their coating methods and in vitro and in vivo performances, and then give insight into the representative biofunctions, i.e. osteointegration, corrosion resistance and biodegradation control, and antibacterial property, provided by CaP coatings for metallic implant materials. Keywords: Calcium phosphates, Metallic implant materials, Surface biofunctionalization, Osteointegration, Biodegradation